Prinsip-Prinsip Situational Pembelajaran (Prinsip-Prinsip Situasional dan Sistem-Sistem Umum Metode Pembelajaran) - Y, Yulianti; Vera, Andi Ana; S, Saprin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine the situational principles of learning and general systems of learning methods. This research uses a qualitative descriptive research method, an approach to studying documents or texts which is a study of written documentary materials that can be in the form of textbooks, newspapers, magazines, letters, films, diary, manuscripts, articles, and the like, material can also come from a person’s mind contained in published books or manuscripts to be analyzed, interpreted, explored to determine the level of achievement of understanding of the topic of a material or text. The result of this literature research is that situational learning principles are guidelines used to design relevant and effective learning experiences by paying attention to the social, cultural, and emotional context of students. The situational principles of learning include: 1) Linkage to Real Life, 2) Cultural and Social Context, 3) Practical Experience, 4) Social Interaction, 5) Flexibility and Adaptation, 6) Application of Technology, 7) Reflection and Feedback, and 8) Emotional Context and Motivation. General systems of learning methods refer to approaches or strategies designed to facilitate the teaching and learning process by taking into account the characteristics of students and educational goals. The following are some common systems of learning methods that are often used in education: 1) Direct Learning, 2) Constructivist Learning, 3) Collaborative Learning, 4) Problem-Based Learning, 5) Project-Based Learning, 6) Online Learning, 7) Differentiated Learning, 8) Contextual Learning, 9) Game-Based Learning, and 10) Emperiential Learning.